Methodology for the selection of an optimal optical sensor for a 6U CubeSat constellation - Chirán-Alpala, William Efrén; Cárdenas-Espinosa, Lorena Paola; Garces-Gomez, Yeison Alberto (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The payload, in defining the central objective of a satellite mission, plays a critical role in determining the overall efficiency of the satellite. Consequently, the satellite's effectiveness is strongly influenced by both the payload itself and its configuration. Given the essential importance of choosing an optimal payload and aware of the direct impact it has on the success of a space mission, this article presents a methodology for selecting an optical sensor intended for the 6U CubeSat constellation of the FACSAT-3 mission and future space missions of the Colombian Aerospace Force (FAC). The methodology includes the definition of mission objectives, definition of key parameters, performance modeling, risk and reliability assessment, and other critical aspects that influence mission efficiency and success.